The Scribner anthology of contemporary short fiction fifty North American stories since 1970 - Williford, Lex 1954-; Martone, Michael (Simon & Schuster, Inc., 1999)
Stories chosen by teachers of college writing-programs, such courses now taught in 800 universities. The stories range from Tim O'Brien's The Things They Carried, a slice of life from the Vietnam War, to Amy Tan's Two Kinds, the efforts of a Chinese-American mother to turn her daughter into a prodigy.